PENINGKATAN HASIL BELAJAR IPS MATERI PENGUATAN EKONOMI MARITIM DAN AGRIKULTUR DI INDONESIA MELALUI MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE STAD SISWA KELAS VIII SMP N 1 BOROBUDUR - Handayani H (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2023)
Reality shows that social studies learning outcomes on Strengthening the Maritime Economy and Agriculture in Indonesia are still not optimal. Indicators less than the optimal role of students in learning include: many student scores do not complete Minimum Completeness Criteria (KKM); students are less active in learning in the classroom; during disorderly student learning; students are less enthusiastic in doing assignments; when the discussion is carried out the interaction between students is less formed; many students complained that the material on Strengthening the Maritime Economy and Agriculture in Indonesia was boring. To overcome this problem, classroom action research (CAR) was conducted using the Cooperative Learning model. The purpose of this study was to improve the learning outcomes of class VIII F students of SMP Negeri 1 Borobudur in the academic year 2022/2023 using the STAD type Cooperative Learning model. The research subjects consisted of 32 students. The source of the research data was obtained from qualitative data in the form of data from observations of teacher and student activities as well as quantitative data in the form of test data on student learning outcomes. The results of the first cycle of research obtained students who completed individually as many as 26 students with classical completeness of 81.25%. While the results of the second cycle research increased with the number of students who completed individually as many as 30 students with a completeness percentage of 93.75%. Based on the results of this study, learning using the Cooperative Learning model type STAD can improve student learning outcomes for class VIII C SMP Negeri 1 Borobudur in the academic year 2022/2023.